Lectotypifications in Micrargeria and Striga (Orobanchaceae) - Arunraj, Parappurakkal Thazhe; Sanjai, Viswanathamandiram Natarajakaimal (Phytotaxa, 2023)
Here we discuss the lectotypification of two names in Micrargeria viz. M. barteri Skan and M. wightii Bentham using the specimens housed at K and two names in Striga viz. S. junodii Schinz and S. welwitschii Engler using the specimens housed at Z and BM respectively. Detailed notes are provided.